Electrolyte imbalance in Asphyxiated term neonates: Incidence, predictors, and outcomes from a prospective cohort study in Northern Uganda - Bahari Yusuf; Tom Ediamu; Simon Odoch; Zeinab Issa Ali; Yasin Ahmed H. Abshir; Abdulahi Abdirizak Farah; Abishir Mohamud Hersi; Ahmed Owjama; Hamdi M. Yusuf; Zakaria Abdi Said; Theoneste Hakizimana; Walyeldin Elfakey; et al. (PLoS ONE, 2026)
Background Birth asphyxia is a major cause of neonatal morbidity and mortality, particularly in low-resource settings. Hypoxia and metabolic derangements that occur during asphyxia predispose neonates to electrolyte abnormalities, which may worsen the clinical course and contribute to poor outcomes. Early recognition and management of such imbalances can improve survival and prevent long-term neurological damage. This study aimed to determine the incidence, predictors, and early outcomes of electrolyte imbalance among term neonates admitted with birth asphyxia in Lira Regional Referral Hospital, Uganda. Methods A hospital-based prospective cohort study was conducted among term neonates admitted with birth asphyxia, defined as a 5-minute Apgar score <7. Serum sodium, potassium, and calcium levels were measured at admission, and repeated on days 3, 7, and 14 for those still admitted. Clinical information including maternal and perinatal characteristics was recorded. Modified Poisson regression (using SPSS) was performed to identify independent predictors of electrolyte imbalance. Early outcomes, including mortality and length of hospital stay, were documented within the first 14 days. Results A total of 152 neonates were enrolled; 52.6% were male. During follow-up, 42 (29.0%) developed hyponatremia, 29 (19.5%) hyperkalemia, and 31 (21.2%) hypocalcemia. Independent predictors of hyponatremia included low Apgar score (0–3), severe hypoxic ischemic encephalopathy (HIE), prolonged intravenous fluid administration (>48 hours), resuscitation at birth, and dehydration. Convulsions, prolonged intravenous fluids, and resuscitation were significantly associated with hypocalcemia, while hyperkalemia was linked to low birth weight and prolonged intravenous fluids (p < 0.05 for all). Mortality was highest among neonates with hyperkalemia, whereas hypocalcemia was significantly associated with prolonged hospital stay (p < 0.05). Conclusion Electrolyte imbalances are common among term neonates with birth asphyxia and hypoxic-ischemic encephalopathy, with hyponatremia, hypocalcemia, and hyperkalemia occurring in nearly one-fifth to one-third of cases. These imbalances are predicted by HIE severity, convulsions, prolonged intravenous fluid therapy, and are associated with increased early neonatal mortality, highlighting the need for routine electrolyte monitoring, standardized intravenous fluid protocols, and timely correction of derangements to improve outcomes.